Screening for Hypoglycemic Activity on the Leaf Extracts of Nine Medicinal Plants: In-Vivo Evaluation - Aditya Arya; Mahmood Ameen Abdullah; Batoul Sadat Haerian; Mustafa Ali Mohd (E-Journal of Chemistry)
The traditional use of certain plants by the tribal community in central India involves using the young leaves for several ailments, including hyperglycaemia; this study was performed to evaluate the effects of the leaf extracts from 9 such plants in the management of diabetes. Initially, hypoglycemic screening was performed on normal rats whose blood glucose levels were measured before and after oral or intraperitoneal (i.p.) administration of the extracts at different periods. The plants were screened at doses of 250 mg/kg i.p. or 500 mg/kg orally. Of these, only Centratherum anthelminticum (Asteraceae), Cissus quadrangularis (Vitaceae), and Woodfordia fruticosa Kurz (Lythraceae) significantly reduced postprandial blood glucose levels in normal glycemic rats (P < 0.001), with slight reductions effected by Sida acuta Burm F. (P = 0.002) and Parthenium hysterophorus L. (P = 0.017). The extracts that reduced postprandial blood glucose levels both orally and i.p. in the hypoglycemic screening tests were evaluated for glucose challenge in glucose tolerance tests with i.p and oral administration in overnight-fasted normal rats. The results of these tests potentiate the screening data in the management of diabetes mellitus, which requires further studies on the plants that yielded positive results to determine the active compounds in the different plant parts that are responsible for the activity.